Synthesis of 4-Hydroxyquinolines as Potential Cytotoxic Agents - Csuvik Oszkár (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2022)
The synthesis of alkyl 2-(4-hydroxyquinolin-2-yl) acetates and 1-phenyl-4-(phenylamino)pyridine-2,6(1H,3H)-dione was optimised. Starting from 4-hydroxyquinolines (4HQs), aminomethylation was carried out via the modified Mannich reaction (mMr) applying formaldehyde and piperidine, but a second paraformaldehyde molecule was incorporated into the Mannich product. The reaction also afforded the formation of bisquinoline derivatives. A new 1H-azeto [1,2-a]quinoline derivative was synthesised in two different ways; namely starting from the aminomethylated product or from the ester-hydrolysed 4HQ. When the aldehyde component was replaced with aromatic aldehydes, Knoevenagel condensation took place affording the formation of the corresponding benzylidene derivatives, with the concomitant generation of bisquinolines. The reactivity of salicylaldehyde and hydroxynaphthaldehydes was tested; under these conditions, partially saturated lactones were formed through spontaneous ring closure. The activity of the derivatives was assessed using doxorubicin-sensitive and -resistant colon adenocarcinoma cell lines and normal human fibroblasts. Some derivatives possessed selective toxicity towards resistant cancer cells compared to doxorubicin-sensitive cancer cells and normal fibroblasts. Cytotoxic activity of the benzylidene derivatives and the corresponding Hammett–Brown substituent were correlated.